New (im)possibilities for agriculture and domestic services in Poland and Italy? Navigating legal solutions and social organisations' support for Ukrainian women displaced by the full-scale invasion of Ukraine in 2022 - Olena Fedyuk; Ivanna Kyliushyk; Iuliia Lashchuk (University of Warsaw, Centre of Migration Research (CMR), 2023)
The aim of this report is to analyse the support provided to Ukrainian women in Poland and Italy displaced as a result of the full-scale Russian invasion of Ukraine in 2022. The analysis focuses on the actions taken by social actors in the agriculture and domestic services sectors. Both countries have been facing labour shortages in these sectors for some time, with the gaps traditionally filled by migrant workers, including a significant number of Ukrainian workers. The main research question is: what forms of support have been provided to forced migrant women from Ukraine in the agriculture and domestic services in Poland and Italy, and has the presence of this new group of migrants contributed to addressing the labour shortages in these sectors? The analysis is based on analysis of secondary sources and the authors' own research findings. We argue that the needs of fleeing Ukrainian women (especially those with children and other dependents) differ significantly from the opportunities available in the agriculture and domestic services in Poland and Italy, characterised by such structural problems as the irregular and seasonal nature of work and working hours, substandard accommodation available for the workers and a lack of work-life balance opportunities. Consequently, there is a need for a more diversified approach to integrating Ukrainian migrant women into the labour markets of the receiving countries. Additionally, it is crucial to adapt legal solutions and implement deeper structural reforms in both sectors to ensure that migrants are protected effectively from exploitation
Keywords: 330; war in Ukraine; forced migration; women; Poland; Italy; support; agriculture; domestic services